Patterns of Talar Articular Facets on Fully Ossified Dry Human Left Calcaneus – An Observational Study - Zaman, Fahmida; Naushaba, Humaira; Khan, Laila Farzana; Akter, Mahbuba (Bangladesh Journal of Anatomy, 2016)
Context: The calcaneus is a weight bearing tarsal bone. It belongs to proximal row and forms the posterior pillar of two longitudinal arches of foot. In the upper surface calcaneus forms talocalcaneal joint with talus which maintains eversion and inversion of foot and named as subtalar joint. There are three facets over upper side of talocalcaneal joint: anterior talar facet, middle and posterior. The aim of this study is to find out the variations in types of talar facets of calcanei. Materials and methods: One hundred and fifty five(155) fully ossified dry human left calcaneus of unknown sex were observed for patterns of talar articular facets at the department of Anatomy, Sir Salimullah Medical College, Dhaka from January 2014 to June 2015. Results: Of the total one hundred and fifty five study samples type I was found in 108 cases (69.68%), type II was found in 44 cases (28.39%) and type III was found in 3 cases (1.93%). Conclusion: The findings of the present study revealed that type I articular facet was common. Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2, pp. 28-31